Effects of organic acids and essential oils blend on growth, gut microbiota, immune response and disease resistance of Pacific white shrimp (Litopenaeus vannamei) against Vibrio parahaemolyticus. Issue 70 (November 2017) - He, Wangquan; Rahimnejad, Samad; Wang, Ling; Song, Kai; Lu, Kangle; Zhang, Chunxiao
Abstract: An 8-week feeding trial was undertaken to evaluate supplemental effects of AviPlus ® (AP), a blend of organic acids [citric acid, 25%; sorbic acid, 16.7%] and essential oils [thymol, 1.7%; vanillin, 1.0%], on growth, gut microbiota, innate immunity and disease resistance of Pacific white shrimp ( Litopenaeus vannamei ) against Vibrio parahaemolyticus . A basal experimental diet was formulated and supplemented with 0, 0.3, 0.6, 0.9 and 1.2 g kg −1  AP to produce five test diets (Con, AP0.3, AP0.6, AP0.9 and AP1.2). Each diet was fed to triplicate groups of shrimp (0.2 ± 0.01 g, mean ± SE) to apparent satiation three times daily. Growth performance and survival rate were not significantly influenced by AP supplementation ( P  > 0.05). Significantly ( P  < 0.05) higher serum total protein was found in groups fed ≥ 0.6 g kg −1  AP compared to control. Serum alkaline phosphatase and phenoloxidase activities were significantly increased in AP0.9 and AP1.2 groups. Also, the group received AP0.6 diet showed significantly higher glutathione peroxidase activity than control. Expression of gut pro-inflammatory genes including TNF-α, LITAF and RAB6A were down-regulated by AP administration. Gut microbiota analysis showed the significant enhancement of the operational taxonomic unit (OTU) diversity and richness indices by AP application. AP supplementation led to increased abundance of Firmicutes and a reduction in abundance of Proteobacteria . Also, dietary inclusion of 1.2 g kg −1  AP led to a significant increase in the abundance of Lactobacillus in shrimp gut. The group offered AP0.3 diet showed significantly higher disease resistance than control group. Furthermore, AP application significantly enhanced relative expression of immune related genes including lysozyme, penaeidin and catalase at 48 h post challenge. In conclusion, these findings show that the tested organic acids and essential oils mixture beneficially affects intestinal microflora and improves immune response and disease resistance of L. vannamei . Highlights: A blend of organic acids and essential oils (AP) was tested in shrimp feed. AP application improved serum phenoloxidase and glutathione peroxidase activities. AP enhanced abundance of Lactobacillus and reduced pathogenic bacteria in shrimp gut. Dietary supplementation of 0.3% AP significantly improved shrimp disease resistance. AP application enhanced expression of immune related genes at 48 h post challenge.